An Exploratory Study on Students’ Experience in Using Chat-GPT for Problem-Based Learning - Trio Ardhian; Taryatman; Khotim Hanifudin Najib; Eka Ridha Nofrida (JIPSINDO, 2026)
This study is motivated by the growing use of artificial intelligence (AI) technology, particularly ChatGPT, to support Problem-Based Learning (PBL). It aims to explore students' experiences in utilizing ChatGPT as a learning aid in PBL, including their perceptions of its effectiveness, encountered challenges, and its impact on critical and independent thinking skills. This research employed a descriptive quantitative approach, involving 176 purposively selected university students as respondents. Data were collected using Likert-scale questionnaires and open-ended questions, then analyzed using descriptive statistics and thematic analysis. The findings indicate that students have positive perceptions toward using ChatGPT across all measured dimensions (Understanding Problems, Planning Solutions, Evaluating Results, Critical Thinking, Collaboration, and Metacognition), with mean scores falling into the high category. Nevertheless, some challenges were identified, such as limited answer accuracy, access constraints, and a tendency toward dependence that might reduce critical thinking engagement. Overall, ChatGPT was perceived as helpful in accelerating material comprehension, enhancing learning independence, and supporting idea development, although its use requires appropriate guidance and sufficient digital literacy. This study highlights the importance of wise AI utilization so it can serve as effective scaffolding to support PBL.